Global burden of chronic kidney disease due to dietary factors - Yin, Lingtao; Kuai, Mengni; Liu, Zhuo; Zou, Binbin; Wu, Ping (Frontiers in Nutrition, 2025)
BackgroundWe aimed to assess the global impact of chronic kidney disease (CKD) attributable to dietary risk factors.MethodsThe research utilized data from the Global Burden of Disease Study 2021 to evaluate age-standardized mortality rates (ASMR), disability-adjusted life years (DALYs), and estimated annual percentage changes (EAPCs) linked to CKD resulting from dietary risk factors.ResultsFrom 1990 to 2021, both the ASMR and age-standardized DALY rate (ASDR) for CKD attributable to dietary risk factors exhibited an overall increasing trend globally. The mortality EAPC was 0.65, while the EAPC for DALYs stood at 0.39. Among dietary risk factors examined, a diet high in sugar-sweetened beverages was associated with the most substantial increase in CKD burden. Notably, Central sub-Saharan Africa bore the highest burden of CKD due to dietary risk factors, with an ASMR of 10.24 and an ASDR of 229.23. The increases in ASMR and ASDR were more pronounced in high-income regions, particularly in Latin America and the Caribbean, where the EAPC values for ASMR were 1.45 and 1.05, respectively, and for ASDR were 1.08 and 0.96. Furthermore, the burden of CKD was notably higher among middle-aged and elderly individuals, especially men aged 65 and above.ConclusionThe global disease burden attributed to dietary risk factors for CKD is increasing. A diet high in sugar-sweetened beverages exerted the most significant impact on CKD. There is a high incidence in Central sub-Saharan Africa, as well as in high-income regions and Latin America and the Caribbean.